SOCIOLINGUISTIC FEATURES OF LITERATURE TRANSLATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Literary translation is not simply a transfer of words but an intricate process involving cultural and social dynamics. Sociolinguistics plays a significant role in interpreting how factors such as culture, identity, and societal norms shape language use in literature and its translation. This paper investigates key sociolinguistic features like dialect, register, cultural allusions, and idioms, addressing how translators deal with the challenge of preserving the original text's social and cultural elements while ensuring that it remains understandable to the target audience. Moreover, the article delves into the ethical complexities translators face in maintaining authenticity, cultural representation, and social nuances during the translation process.